Plant closures in Australia's automotive industry: continuity and change. Issue 1 (31st December 2022) - Irving, Jacob; Beer, Andrew; Weller, Sally; Barnes, Tom
ABSTRACT: This paper explores the possibility of using diachronic case study comparisons to shed light on continuity and change in policy interventions to manage plant closures. It compares the early results of a survey of workers retrenched in the 2017 closure of Australia's passenger vehicle manufacturing industry with the results of a similar survey of workers who lost their jobs in the 2005 closure of Mitsubishi's Adelaide engine-casting and components plant. Despite the 12 years of accumulated expertise in plant closure and structural adjustment management, this comparison shows remarkable similarities in the profile of the cohort of retrenched workers and remarkable similarities in their employment outcomes. The discussion reflects on conditions that produce continuity and change.